DINAMIKA PELAKSANAAN PROGRAM EDUPRENEURSHIP DALAM MENGEMBANGKAN EKONOMI KEWARGANEGARAAN - Ari Wahyu Kusumajati; Deni Zein Tarsidi; Joko Daryanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study focuses on analyzing the dynamics of edupreneurship implementation within educational institutions, particularly schools, and its contribution to the formation of civic economy among students. Edupreneurship in the field of education refers to creative and innovative efforts by institutions to instill entrepreneurial spirit, independence, and competitiveness for students’ future lives. The method used in this research is qualitative approach with literature study type of research. This study employs qualitative data and secondary data sources. The findings show that the dynamics of edupreneurship program implementation are characterized by three main aspects: (1) integration of relevant curriculum, (2) paradigm shifts among educators, and (3) creation of a practical ecosystem. Edupreneurship has proven to be one of the solutions to the problem of educated unemployment and serves as an effective way to prepare active and productive citizens in the economy through the development of soft skills in schools.